Gut Microbiota and Chemical-Induced Acute Liver Injury - Chen, Tao; Li, Rui; Chen, Peng (Frontiers in Physiology, 2021)
Drug overdose or chemical exposures are the main causes of acute liver injury (ALI). Severe liver injury can develop into liver failure that is an important cause of liver-related mortality in intensive care units in most countries. Pharmacological studies have utilized a variety of comprehensive chemical induction models that recapitulate the natural pathogenesis of acute liver injury. Their mechanism is always based on redox imbalance-induced direct hepatotoxicity and massive hepatocyte cell death, which can trigger immune cell activation and recruitment to the liver. However, the pathogenesis of these models has not been fully stated. Many studies showed that gut microbiota plays a crucial role in chemical-induced liver injury. Hepatotoxicity is likely induced by imbalanced microbiota homeostasis, gut mucosal barrier damage, systemic immune activation, microbial-associated molecular patterns, and bacterial metabolites. Meanwhile, many preclinical studies have shown that supplementation with probiotics can improve chemical-induced liver injury. In this review, we highlight the pathogenesis of gut microorganisms in chemical-induced acute liver injury animal models and explore the protective mechanism of exogenous microbial supplements on acute liver injury.